Head morphology in perinatal dolphins: A window into phylogeny and ontogeny - Rauschmann, Michael A.; Huggenberger, Stefan; Kossatz, Lars Swen; Oelschläger, Helmut H. A. (Journal of Morphology, 2006)
In this paper on the ontogenesis and evolutionary biology of odontocete cetaceans (toothed whales), we investigate the head morphology of three perinatal pantropical spotted dolphins (Stenella attenuata) with the following methods: computer-assisted tomography, magnetic resonance imaging, conventional X-ray imaging, cryo-sectioning as well as gross dissection. Comparison of these anatomical methods reveals that for a complete structural analysis, a combination of modern imaging techniques and conventional morphological methods is needed. In addition to the perinatal dolphins, we include series of microslides of fetal odontocetes (S. attenuata, common dolphin Delphinus delphis, narwhal Monodon monoceros). In contrast to other mammals, newborn cetaceans represent an extremely precocial state of development correlated to the fact that they have to swim and surface immediately after birth. Accordingly, the morphology of the perinatal dolphin head is very similar to that of the adult. Comparison with early fetal stages of dolphins shows that the ontogenetic change from the general mammalian bauplan to cetacean organization was characterized by profound morphological transformations of the relevant organ systems and roughly seems to parallel the phylogenetic transition. from terrestrial ancestors to modern odontocetes.